State of the helium atom inside a fullerene - Poteryaeva, Valentina A.; Bubenchikov, Mikhail A.; Bubenchikov, Alexey M.; Potekaev, Aleksandr I. 1951-; Kaparulin, Dmitry S. (Russian physics journal)
The problem of motion of the helium atom inside the fullerene molecule at ultralow temperatures is considered. The solution of the Schrodinger equation is obtained by numerical methods using special functions. The potential energy of interaction of the fullerene particle with the helium atom is calculated by integrating the modified Lennard-Jones potential over the idealized surface of the hollow nanoparticle. As a result of calculations, zones of the most probable localization of the atomic particle in the states with (n, m, and k(n)) inside the C-60 fullerene were determined and visualized.